IMPLEMENTATION OF THE INTERNET OF THINGS (IOT) FOR REMOTE LIGHT CONTROL USING NODEMCU ESP8266 AND THINGSPEAK VIA WEBSITE-BASED INTERNET - Winda Suci Lestari Nasution; Patriot Nusa (LPPM Universitas Widya Dharma, 2023)
Currently the existence of the internet has an impact on community interaction, social life, communication and culture. The internet connects many devices, one of which is lights. The lamp is a life support tool that plays an important role as a substitute for sunlight. Currently, the use of lamps in society is considered less effective and the use of lamps is often neglected. Often found lights that are on but not used (wasteful). On the other hand, the process of turning off and turning on the lights manually is very inconvenient, so it is a waste of time. Therefore, a lamp control system and a system that can monitor the use of lamps are made more effectively and efficiently using the Internet of Things (IoT). The Internet of Things is defined as the interconnection of embedded computing devices, and this interconnection is identified by the existence of the Internet infrastructure. With this system, it is expected to be able to overcome problems in knowing the conditions and controlling lights remotely using Nodemcu Esp8266 and Thingspeak Via Internet-Based Website. In this study, researchers used Experiments as a research method and SDLC as a method of developing Internet of Things (IoT) devices. The result of this research is a website-based light control system (LED) using NodeMCU ESP8266, Thingspeak, and Arduino IDE.